A new paramagnetically shifted imaging probe for MRI. Issue 3 (28th February 2016) - Senanayake, P. Kanthi; Rogers, Nicola J.; Finney, Katie‐Louise N.A.; Harvey, Peter; Funk, Alexander M.; Wilson, J. Ian; O'Hogain, Dara; Maxwell, Ross; Parker, David; Blamire, Andrew M.
Abstract : Purpose: To develop and characterize a new paramagnetic contrast agent for molecular imaging by MRI. Methods: A contrast agent was developed for direct MRI detection through the paramagnetically shifted proton magnetic resonances of two chemically equivalent tert ‐butyl reporter groups within a dysprosium(III) complex. The complex was characterized in phantoms and imaged in physiologically intact mice at 7 Tesla (T) using three‐dimensional (3D) gradient echo and spectroscopic imaging (MRSI) sequences to measure spatial distribution and signal frequency. Results: The reporter protons reside ∼6.5 Å from the paramagnetic center, resulting in fast T 1 relaxation ( T 1  = 8 ms) and a large paramagnetic frequency shift exceeding 60 ppm. Fast relaxation allowed short scan repetition times with high excitation flip angle, resulting in high sensitivity. The large dipolar shift allowed direct frequency selective excitation and acquisition of the dysprosium(III) complex, independent of the tissue water signal. The biokinetics of the complex were followed in vivo with a temporal resolution of 62 s following a single, low‐dose intravenous injection. The lower concentration limit for detection was ∼23 μM. Through MRSI, the temperature dependence of the paramagnetic shift (0.28 ppm.K −1 ) was exploited to examine tissue temperature variation. Conclusions: These data demonstrate a new MRI agent with the potential for physiological monitoring by MRI. Magn Reson Med 77:1307–1317, 2017. © 2016 The Authors Magnetic Resonance in Medicine published by Wiley Periodicals, Inc. on behalf of International Society for Magnetic Resonance in Medicine. This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.